Architecture of the Molecules of Life, a Contribution of Louis Pasteur to Molecular Pharmacology; Opportunities for Adrenergic Pharmacology Developments - Garcia Huidobro-Toro, J (centre Mersenne pour ldition scientifique ouverte, 2020)
When Louis Pasteur observed para tartaric acid crystals under the microscope. he noted right- and left-handed tiny crystals, which when manually separated resulted in the same optical activity but of opposite sign. This seminal observation was correctly interpreted indicating that para tartaric acid was the mixture of two different molecules: a finding that was later recognised as an essential code of molecular pharmacology based on the 3D spatial configuration of molecules. An immediate application of this concept refers to natural products such as morphine or ephedrine, both of which have the precise stereochemistry to fit and selectively activate the a-opiate receptor or alpha-adrenoceptor mechanisms, respectively, and their associated intracellular signalling mechanisms. In this essay, we review the past, present and future of stereochemistry notions and its significance for adrenergic pharmacology, highlighting the relevance of optical isomers of sympathomimetics or beta-adrenoceptor antagonists. The principle of optical activity revealed by Pasteur challenges the pharmaceutical industry to identify biologically active chemicals identifying the relevant stereochemical isomer responsible for drug efficacy and safety. It is no overstatement that pain is alleviated worldwide by a single stereochemical morphine isomer, that is synthesised by the poppy plant, which interacts stereospecifically with the relevant opioid receptor(s) highlighting Pasteur s brilliant discovery to the principles of molecular pharmacology.